Lost on the Way: Nonresponse and its Influence on Turnout Bias in Postelection Surveys. (29th December 2015) - Sciarini, Pascal; Goldberg, Andreas C.
Abstract: Earlier studies on turnout bias in postelection surveys have focused on vote overreporting (measurement bias) and have disregarded nonresponse bias associated with voter overrepresentation. Based on a unique data set of validated votes collected for two different ballots, we offer an in-depth analysis of the size and sources of nonresponse bias. On the aggregate level, we find that voter overrepresentation accounts for a larger share of total turnout bias than misreporting. On the individual level, past voting record, ballot vote, and age appear as strong predictors of survey participation. Breaking down further the analysis, we show that these factors contribute to nonresponse bias through both contact and cooperation. By contrast, the effects of some other factors work at cross-purpose in the contact and cooperation stages.